2000
DOI: 10.1097/00126334-200011010-00002
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Cellular Immunity Against Tuberculosis in Patients Coinfected With HIV-1 and Tuberculosis With Effective Antiretroviral Therapy: Assessment by Determination of CD69 Expression on T Cells After Tuberculin Stimulation

Abstract: Whether immunity against opportunistic pathogens can be fully restored by control of HIV-1 replication remains open to question. This longitudinal study was conducted to measure anti-tuberculosis (TB) cellular immunity in 13 HIV-1/TB-coinfected patients effectively treated by highly active antiretroviral therapy (HAART) in a period of 12 months. In this study, anti-TB cellular immunity was assessed by determining the frequencies of CD 69 expression on CD4+ and CD8+ T cells in response to purified protein deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…In fact, although it has been demonstrated that HAART can induce restoration of in vitro response to mycobacterial antigen [25], studies conducted in patients co-infected with HIV and tuberculosis suggest that recovery of cellular immunity against tuberculosis may be delayed, incomplete or absent in some individuals who have a good immunological and virological response to antiretroviral therapy [26,27], particularly when HAART is started at low CD4 lymphocytes count [24]. However, when interpreting data on CD4 lymphocyte counts at the time of diagnosis of tuberculosis it should be taken into account that active tuberculosis itself can cause immunosuppression, as suggested by the transient decrease in CD4 lymphocytes observed in a significant proportion of HIV-negative patients with tuberculosis [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, although it has been demonstrated that HAART can induce restoration of in vitro response to mycobacterial antigen [25], studies conducted in patients co-infected with HIV and tuberculosis suggest that recovery of cellular immunity against tuberculosis may be delayed, incomplete or absent in some individuals who have a good immunological and virological response to antiretroviral therapy [26,27], particularly when HAART is started at low CD4 lymphocytes count [24]. However, when interpreting data on CD4 lymphocyte counts at the time of diagnosis of tuberculosis it should be taken into account that active tuberculosis itself can cause immunosuppression, as suggested by the transient decrease in CD4 lymphocytes observed in a significant proportion of HIV-negative patients with tuberculosis [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Expression of CD69 on lymphocytes has been shown to be associated with cellular immune function in patients with a variety of other conditions (6,17,22,25). In addition, other rapid assays have been found to be useful in determining the cellular immune response in patients with other granulomatous conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A significantly higher level of expression of CD69 was found in patients with TB 8 months after they started treatment compared to that in healthy controls (26). Furthermore, in patients coinfected with HIV type 1 and M. tuberculosis, the expression of CD69 correlated with the results of TST and IFN-␥ production in PPD-stimulated CD4 T lymphocytes (15). Because little is known about CD69 antigen expression on CD4 T lymphocytes after in vitro tuberculin stimulation in patients with proven active TB before treatment and individuals with clinically inactive TB and a history of a previous episode of TB, we designed a study to evaluate the expression of CD69 on CD4 T lymphocytes using flow cytometry.…”
mentioning
confidence: 86%